A Flexible Extension of Reduced Kies Distribution: Properties, Inference, and Applications in Biology. (5th October 2022) - Almuqrin, Muqrin A.; Gemeay, Ahmed M.; El-Raouf, M. M. Abd; Kilai, Mutua; Aldallal, Ramy; Hussam, Eslam
Abstract : The extended reduced Kies distribution (ExRKD), which is an asymmetric flexible extension of the reduced Kies distribution, is the subject of this research. Some of its most basic mathematical properties are deduced from its formal definitions. We computed the ExRKD parameters using eight well-known methods. A full simulation analysis was done that allows the study of these estimators' asymptotic behavior. The efficiency and applicability of the ExRKD are investigated via the modeling of COVID-19 and milk data sets, which demonstrates that the ExRKD delivers a better match to the data sets when compared to competing models.